Upaya meningkatkan minat dan hasil belajar matematika melalui pembelajaran matematika realistik pada materi KPK (kelipatan persekutuan terkecil) siswa Kelas IV MIN 9 Aceh Barat Daya - Nurasmawati, Nurasmawati (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this study is to improve the activities and learning outcomes of Mathematics in KPK grade IV MIN 9 Aceh Barat Daya. The study was conducted at MIN 9 Aceh Barat Daya. The model used in this study is Realistic Mathematics Learning. The subjects of this study were students in grade IV MIN 9 Southwest Aceh. The number of students is 13 students with 6 male students and 7 female students. This research was conducted in the 2019/2020 Academic Year within a period of 3 months, from September 2019 to November 2019 in Odd Semester. The methodology of this research is class-room action research consisting of two cycles and each cycle consists of two meetings. In each cycle consists of planning, implementation, observation and reflection. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Observation data is done by observing the activeness of stu-dents in the learning process. Data were analyzed by means of percentage statistics. Indicators of student learning outcomes that reach the Minimum Mastery Criteria (KKM) is 65. The results of the study indi-cate that an increase in learning outcomes in each cycle, namely in the pre-cycle (before action) with an average value of 60.76 and the percentage of completeness classically by 46.15% or 6 students who have achieved mastery learning. In Cycle I with an average value of 70.76 and the percentage of com-pleteness classically 61.53% or 8 students who have achieved mastery learning. While in Cycle II with an average value of 81.53 and the percentage of completeness classically 76.92% or 10 students who have achieved mastery learning. Student learning activities have increased from enough categories to be good and good categories increased to very good. Based on the description that has been stated above it can be concluded that the application of Realistic Mathematics Learning can improve Mathematics learning activities and outcomes in KPK grade IV MIN 9 Southwest Aceh Academic Year 2019/2020.